Propriedades elétricas e fotoelétricas de Nanofitas de SnO2 - Emilson Ribeiro Viana Junior (2014)
A study of the electrical and photoelectrical properties of isolated SnO2 nanobelts is presented in this theses. The nanobelts were grown by the vaporliquid- solid method and, by using optical lithography, were fabricated fieldeffect- transistors in order to study the nanobelt´s electrical transport in different temperatures and atmospheric conditions. At first, the morphology and crystal structure of the nanobelts were studied by Scanning Electron Microscopy, Atomic Force Microscopy, Transmission Electron Microscopy and X-ray Diffraction. Them, devices of isolated nanobelts were fabricated. The electrical transport of individual nanobelts was measured in darkness by measuring the resistivity as a function of temperature. Several models were used to analyze the experimental data in different temperature regions: thermally activated conduction in the conduction band, nearest-neighbor hopping conduction in a defect band and variable range hopping conduction in a defect band. Through these studies it was possible to show that despite to the expected 1D transport in this thin nanoestructures, the nanobelts behave as a three-dimensional system from the hopping conduction point of view. The conductivity of the nanobelts was also measured as a function of temperature under ultra-violet illumination. Calculations of the photo-induced charge density is so high that for temperatures higher than 150 K it exceed the Mott critical density and the nanobelt transit from the insulating or semiconducting state to the metallic state. This metal-insulator transition was experimentally observed at 240 K. The observation of this transition demonstrate the potential of these nanostructures for applications in new kind of electronic devices. This phenomena was attributed to the large degree of disorder in the nanobelts. The effect of the quantization of the conduction in the conduction band of was observed in the nanobelts trough oscillations in the source current vs. gate voltage curve of the transistors, at low temperatures. The quantum confinement of electrons creates energy sub-bands that are filled by changing the Fermi level in the material with the gate voltage. A maximum energy separation of 5.5 meV was estimated between the sub-bands, in agreement with the flattening of the current oscillations for temperatures above 50 K. The photoconductivity of SnO2 nanobelts was measured as a function of temperature and in different atmospheres: air, helium, vacuum. Under ultraviolet illumination it was observed a fast and strong enhancement of the photoconductivity. This effect is enhanced at low temperature and low oxygen concentrations in the atmosphere. When the light is turned off the induced photocurrent slowly decays with lifetimes up to several hours, characterizing the Persistent Photoconductivity effect. This effect was explained in terms of the adsorption and desorption of molecular oxygen at the surface of the nanobelts. The temperature dependence of the persistent photoconductivity was explained in terms of the thermal activation of holes from a shallow acceptor to the valence band of the material, with activation energy of 230 meV.